PERSEPSI KUALITAS LAYANAN WARUNG INTERNET DI KOTA MEDAN - Winarto Winarto (Universitas Methodist Indonesia, 2017)
The purpose of the research is to examine the service quality perception of Internet cafe in Medan City. The research has been conducted in 30 Internet cafe, used a convenience sampling method to survey 286 respondents. The questionnaire measures five dimensions of service quality; tangible, reliability, responsiveness, assurance and empathy. Overall, the perception of service quality of Internet Cafe in Medan city is adequately good. Finally, implications and suggestions for future research are discussed.